FACTORS THAT INFLUENCE GRATITUDE - Wibowo, Agung; Rusyda, Arina Ilfa; Ramyana, Fitriyani; Imtinan, Ghina; Riady, Muhammad Antos (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Gratitude is an expression of gratitude to Allah SWT for the favors, gifts, and conveniences given. Gratitude is divided into gratitude in heart, words, and deeds. This study aims to determine the factors that influence gratitude by using a literature review technique. Literature search was carried out on electronic databases, google scholar, and google with the keyword gratitude. The results of this search indicate that there are two factors that influence gratitude. These factors are internal factors and external factors. Internal factors consist of religiosity, remembering God's favors, all favors will be held accountable, seeing people who are lower in rank, praying to be given help to be grateful, emotionality, prosociality, positive affect, good intentions, and the presence of psychopathology within. While external factors in the form of perceptions of peers and family roles.